Zoop to poop: assessment of microparticle loads in gray whale zooplankton prey and fecal matter reveal high daily consumption rates - Torres, Leigh G.; Brander, Susanne M.; Parker, Julia I.; Bloom, Elissa M.; Norman, Robyn; Van Brocklin, Jennifer E.; Lasdin, Katherine S.; Hildebrand, Lisa (Frontiers in Marine Science, 2023)
The ocean continues to be a sink for microparticle (MP) pollution, which includes microplastics and other anthropogenic debris. While documentation of MP in marine systems is now common, we lack information on rates of MP ingestion by baleen whales and their prey. We collected and assessed MP loads in zooplankton prey and fecal samples of gray whales (Eschrichtius robustus) feeding in coastal Oregon, USA and produced the first estimates of baleen whale MP consumption rates from empirical data of zooplankton MP loads (i.e., not modeled). All zooplankton species examined were documented gray whale prey items (Atylus tridens, Holmesimysis sculpta, Neomysis rayii) and contained an average of 4 MP per gram of tissue, mostly of the microfiber morphotype. We extrapolated MP loads in zooplankton prey to estimate the daily MP consumption rates of pregnant and lactating gray whales, which ranged between 6.5 and 21 million MP/day. However, these estimates do not account for MP ingested from ambient water or benthic sediments, which may be high for gray whales given their benthic foraging strategy. We also assessed MP loads in fecal samples from gray whales feeding in the same spatio-temporal area and detected MP in all samples examined, which included microfibers and significantly larger morphotypes than in the zooplankton. We theorize that gray whales ingest MP via both indirect trophic transfer from their zooplankton prey and directly through indiscriminate consumption of ambient MPs when foraging benthically where they consume larger MP morphotypes that have sunk and accumulated on the seafloor. Hence, our estimated daily MP consumption rates for gray whales are likely conservative because they are only based on indirect MP ingestion via prey. Our results improve the understanding of MP loads in marine ecosystems and highlight the need to assess the health impacts of MP consumption on zooplankton and baleen whales, particularly due to the predominance of microfibers in samples, which may be more toxic and difficult to excrete than other MP types. Furthermore, the high estimated rates of MP consumption by gray whales highlights the need to assess health consequences to individuals and subsequent scaled-up effects on population vital rates.